2022
DOI: 10.3389/fped.2022.993811
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination completeness in children with rheumatic diseases: A longitudinal, observational multicenter cohort study in Switzerland

Abstract: IntroductionChildren with pediatric inflammatory rheumatic diseases (PRD) have an increased infection risk. Vaccinations are effective to avoid vaccine-preventable diseases. This study aimed to assess the vaccination completeness in Swiss PRD patients stratified by immunosuppressive treatment (IST).Materials and methodsThis multicenter observational cohort study of PRD patients was performed in Basel, Geneva, Lucerne, Lausanne, and Zurich in PRD patients aged < 18 years included in the Juvenile Inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Incomplete vaccination in JIA and pediatric rheumatic disease patients were reported in several previous studies[ 18 , 19 , 30 , 31 , 32 ]. From the medical point of view, the main predictors of incomplete vaccination were polyarticular and systemic JIA categories and immunosuppressive medications[ 30 , 31 , 33 ]. In our previous study, the younger JIA onset age was associated with a higher proportion of omitted vaccines similar to the study of Minden et al [ 18 ], but some authors reported that preschool children had a similar rate of vaccine coverage as healthy peers[ 30 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Incomplete vaccination in JIA and pediatric rheumatic disease patients were reported in several previous studies[ 18 , 19 , 30 , 31 , 32 ]. From the medical point of view, the main predictors of incomplete vaccination were polyarticular and systemic JIA categories and immunosuppressive medications[ 30 , 31 , 33 ]. In our previous study, the younger JIA onset age was associated with a higher proportion of omitted vaccines similar to the study of Minden et al [ 18 ], but some authors reported that preschool children had a similar rate of vaccine coverage as healthy peers[ 30 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Usually, decreased vaccine coverage correlated with patients’ age and teens had more omitted vaccines than preschools[ 18 , 30 , 32 , 33 ]. In our study, the proportion of patients, who received vaccination against pneumococcus was the highest in the IBD subgroup.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations